2014
DOI: 10.1021/jp5058622
|View full text |Cite
|
Sign up to set email alerts
|

Competing Salt Effects on Phase Behavior of Protein Solutions: Tailoring of Protein Interaction by the Binding of Multivalent Ions and Charge Screening

Abstract: The phase behavior of protein solutions is affected by additives such as crowder molecules or salts. In particular, upon addition of multivalent counterions, a reentrant condensation can occur; i.e., protein solutions are stable for low and high multivalent ion concentrations but aggregating at intermediate salt concentrations. The addition of monovalent ions shifts the phase boundaries to higher multivalent ion concentrations. This effect is found to be reflected in the protein interactions, as accessed via s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 57 publications
3
53
0
Order By: Relevance
“…This work, at a microscopic level, echoes experimental results showing the existence of reentrant condensation in HSA solutions in the presence of trivalent ions [18][19][20] and is also in agreement with recent calorimetry experiments. 45 Different models were used: an atomic model, a coarse-grained model, and a colloidal The colloidal model was used to study the interactions of two spherical colloids representing HSA-like molecules.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This work, at a microscopic level, echoes experimental results showing the existence of reentrant condensation in HSA solutions in the presence of trivalent ions [18][19][20] and is also in agreement with recent calorimetry experiments. 45 Different models were used: an atomic model, a coarse-grained model, and a colloidal The colloidal model was used to study the interactions of two spherical colloids representing HSA-like molecules.…”
Section: Resultssupporting
confidence: 91%
“…17 HSA solutions undergo reentrant condensation upon addition of trivalent salts (YCl 3 , LaCl 3 , FeCl 3 , or AlCl 3 ). [18][19][20] That is, upon increase of the trivalent salt concentration, protein aggregation is first observed, then redissolution of the samples occurs. This anomalous trend, caused by charge reversal, has been shown to be able to induce clustering, liquid-liquid phase separation or crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies of globular proteins in solutions containing multivalent metal ions have revealed complex phase behavior including reentrant condensation (RC), metastable liquid-liquid phase separation (LLPS) and crystallization. 34,[37][38][39][40][41][42][43] A similar experimental phase diagram, like the one shown in Fig. 2, has been observed for several proteins in solution in the presence of trivalent metal ions.…”
Section: Experimental Phase Diagram Of Blg With Cdcl 2 or Znclsupporting
confidence: 79%
“…The dashed red line corresponds to the first derivative of the area of Bragg peaks as a function of time (right axis). (b) BLG 33 mg ml À1 with 20 mM CdCl 2 .Faraday Discussions Paper52 | Faraday Discuss., 2015, 179,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] This journal is © The Royal Society of Chemistry 2015Open Access Article. Published on 12 January 2015.…”
mentioning
confidence: 99%
“…In molecular biology, the ions can be broadly grouped into two categories: mobile ions in the water phase and ions bound to the corresponding macromolecule. The mobile ions in the solvent freely move in response to electrostatic environment and their major role is to provide screening of electrostatic interactions [4,5]. On the other hand, the ions bound to macromolecules are involved in specific interactions with macromolecular moiety and play roles in catalysis, electron/proton transfer reactions and structural stability [6][7][8].…”
Section: Introductionmentioning
confidence: 99%